ESTIMATION OF HEAVY METALS (Cd, Cu, Pb, Zn) FROM SIX SPECIES OF VESPER BATS - S. Nighat; M. S. Nadeem; S. I. Shah; R. Z. Bhatti; N. Akhter; T. Mahmood; A. Aihetasham; M. Asif; A. Javid (Journal of Animal and Plant Sciences, 2019)
Metals play an important role in the biological functions of our body, but their bio toxic effects can be harmful and can disturb the normal body functions. Metals are elevating in the environment due to rapid industrialization, and other anthropogenic activities. Toxic metals are bio accumulated by insectivorous bats due to their foraging habits and high trophic level. As the bio-accumulation of toxic pollutants is one of the major reasons of bat decline in the world, this study was carried out to quantify heavy metal concentrations in the kidney, liver, and heart of micro-bats collected from different areas of Punjab, Pakistan. Our findings showed significant difference in Cd, Cu, Pb and Zn concentrations in liver, heart and kidneys. Significant differences were observed for Pb and Zn concentrations in the liver of the six species under observation while Cu and Pb levels in the kidney and heart varied significantly. This study provides a base for future monitoring of metals in bats for management.
Keywords: Metals; Bats; Vespertilionidae; Chiroptera